How implementing SCM affect different manufacturing companies? - Ab. Rahman, Mohd Nizam; Manzouri, Malihe; Arshad, Haslina; Nordin, Norani (Inderscience Enterprises Ltd., 2013)
Presenting products with a shorter life cycle, intense competition among enterprises and the highest level of customer satisfaction, have forced organisations to invest more on their supply chain. Managers always tried to design effective business to meet customer demands better than competitors.So, understanding the main issues related to supply chain management (SCM) implementation can help managers to make an effective strategy in managing their customers' demands and fulfilling suppliers' requirements.The purpose of this paper is to discuss the important problematic issues which hinder companies to implement SCM. To achieve these goals implementing SCM in two important industries in Malaysia (automotive and food) have been considered.A questionnaire was used to identify the perceived problems and attitudes towards SCM. The questionnaire was distributed to 600 food and automotive organisations in Malaysia.A total of 62 usable replies were received from the automotive industry, and 140 from the food organisations. Structured interviews were used to find out how problematic issues in these organisations could be overcome.The key problems were identified as: a lack of information (automotive industry) and high costs (food industry).Benchmarking from experienced companies and conducting training courses were identified as important methods to reduce these problems.